The American Pageant / A History of the Republic; Volume II - Bailey Thomas A.; Kennedy David M (D.C. Heath And Company, 1983)
The Order of Reconstruction, Politics in the Gilded Age - 1869-1889, Industry Comes of Age - 1865-1900, New Social and Cultural Horizons - 1865-1900, The Path of Empire, Progressivism and the Republican Roosevelt, Woodrow Wilson and the New Freedom, The Road to World War I, Making and Unmaking the Peace, The Great Depression and the New Deal, America in World War II, Korea and the Eisenhower Era, The Rise and Fall of Richard Nixon, The American People Since World War II, Color Portfolios, Index.
The Order of Reconstruction, Politics in the Gilded Age - 1869-1889, Industry Comes of Age - 1865-1900, New Social and Cultural Horizons - 1865-1900, The Path of Empire, Progressivism and the Republican Roosevelt, Woodrow Wilson and the New Freedom, The Road to World War I, Making and Unmaking the Peace, The Great Depression and the New Deal, America in World War II, Korea and the Eisenhower Era, The Rise and Fall of Richard Nixon, The American People Since World War II, Color Portfolios, Index.